Biofabrication and artificial intelligence strategies for investigating solid- and fluid-pressure mechanobiology in pancreatic ductal adenocarcinoma - Yahui Ding; Peiyuan Zhao; Yan Jin; Yan Li; Zifei Wang; Ye Lu; Yichen Zhang; Hongzhuan Chen; Weidong Zhang; Xin Luan; Min Tang (Cancer and Metastasis Reviews, 2026)

Hopanoids reveal a shift from natural to anthropogenic petrogenic organic carbon in the East China Sea - Yanhong Xu; Zhongqiang Ji; Peisong Yu; Dong Xu; Dewang Li; Weiyan Zhang; Lelong He; Ningxiao Yu; Yongge Sun; Haiyan Jin (Acta Oceanologica Sinica, 2026)

Extreme drought-induced significant reduction of particulate organic carbon (POC) and its impact on apparent oxygen utilization (AOU) in the Changjiang Estuary and adjacent East China Sea - Ningxiao Yu; Haiyan Jin; Zhongqiang Ji; Dewang Li; Pengbin Wang; Bin Wang; Zhi Yang; Ling Chen; Ying Luo; Jiaqin Chen; Qianwen Sun; Jiangning Zeng; et al. (Marine Pollution Bulletin, 2026)

Vertical textural contract (VTC) increases seawater evaporation from heterogeneous sand - Jing Yan; Wenjuan Zheng; Yan Jin (Advances in Water Resources, 2025)

Enhancement of rice production and soil carbon sequestration utilizing nitrogen-fixing cyanobacteria - Sen Li; Weigen Huang; Chengrong Peng; Xiaoyan Jing; Jixian Ding; Tong Chen; Ruilin Huang; Han Hu; Jizhong Zhou; Jiabao Zhang; Yuting Liang (Applied Soil Ecology, 2025)

Potential Functions of the Gut Microbiome and Modulation Strategies for Improving Aquatic Animal Growth - Zhimin Zhang; Qiushi Yang; Haokun Liu; Junyan Jin; Yunxia Yang; Xiaoming Zhu; Dong Han; Zhigang Zhou; Shouqi Xie (Reviews in Aquaculture, 2025)
The increase in the body weight of animals, a pivotal indicator closely tied to production, is important to the aquaculture industry. Despite remarkable variability in gut microbiomes, which are intricately associated with their hosts and affect overall performance, fitness, and physiological outcomes, across individuals and species, the development and practical application of gut microbiota modulation in aquaculture remain underdeveloped. In this review, we systematically examine the advancements with a focus on the gut microbiomes of aquatic animals with different growth rates by literature search, summarizing the existing knowledge regarding the diversity, composition, and significance of the microbiome in individual growth. The comparative analysis reveals substantial alterations in the gut microbiome that correspond to changes in the growth rate of aquatic animals, with a species bias toward more carnivorous fish, and shrimps and sea cucumbers in nonfish species. The present review also discusses comparative gut microbiome research in aquaculture as an emerging field with great potential for advancing our understanding of animal growth, screening candidate probiotics, and facilitating microbiome modulation strategies. Besides, the present gaps in the knowledge of the gut microbiome associated with the growth and production of farmed animals have been highlighted. We propose potential directions to address emerging challenges and opportunities in this field, such as priority effects on gut microbiome establishment, especially in the early stage, and screening of host‐derived probiotics across various aquatic animals. Finally, we provide a conceptual framework for enhancing animal farming practices in aquaculture through intensified gut microbiome research.